ANTIOXIDANT ACTIVITY OF FACIAL MOISTURIZING FORMULATIONS FROM VARIOUS PLANTS - Holanda, Helen; Marcella, Eveline; Pratami, Intan; Pebriyanti, Sindi; Novitasari, Fitria; Imania, Syaila (HEARTY, 2025)
Indonesia, with its rich biodiversity, has great potential in medicinal plants that can be utilized in cosmetic products. The use of natural ingredients in cosmetics, such as moisturizers, is increasingly in demand because of its ability to improve skin health at a relatively lower cost. Moisturizers function to overcome dry skin problems and maintain skin moisture by reducing water loss and protecting it from environmental impacts. This study aims to identify plants with potential antioxidant activity for use in facial moisturizer formulations. The method used is a literature review from various sources, including journals and publications related to antioxidant activity. The results showed that Purple Sweet Potato Leaves (Ipomoea batatas) and Celery (Apium graveolens) have very strong antioxidant activity with IC50 values of 3.68 ppm and 19.66 ppm, respectively. Sonneratia caseolaris leaves also showed strong antioxidant activity with an IC50 value of 14.503 ppm. Other plants such as Virgin Coconut Oil (Cocos Nucifera), Malacca Fruit (Phyllanthus emblica), and Carrot Root (Daucus Carota) also have significant antioxidant activity, although with higher IC50 values. In conclusion, these plants show great potential for use in cosmetic formulations that can combat oxidative stress and maintain skin health.